Znajomość języków obcych a wymagania zmieniającego się rynku pracy: wyniki badania pilotażowego przeprowadzonego w trzech warszawskich przedsiębiorstwach - Wojakowska , Marta (Neofilolog, 2025)
The development of the economy, the technological transformation and the digitalization of services and products present us with new tasks. Are foreign languages still among these competencies, as they were in the early 2000s? We look for answers to these and other key questions in interviews conducted with those responsible for language training in Warsaw companies in the advertising and marketing industry, and in surveys conducted among their employees. In the first part of the article, we present the context of the study on new competencies sought for in the labor market today. Following a synthetic presentation of the theoretical background to the research questions, the paper considers the perceptions of employees and employers on the relevance and usefulness of language classes in the workplace. This is followed by a discussion of the study findings presenting the conclusions and observations on language courses in the time of a changing labor market.